Sick Leave—A Signal of Unequal Work Organizations? Gender perspectives on work environment and work organizations in the health care sector: a knowledge review - Vänje, Annika (Nordic Journal of Working Life Studies, 2015)
The background to this article review is governmental interest in finding reasons why a majority of the employees in Sweden who are on sick leave are women. In order to find answers to these questions three issues will be discussed from a meso-level: (i) recent changes in the Swedish health care sector’s working organization and their effects on gender, (ii) what research says about work health and gender in the health care sector, and (iii) the meaning of gender at work. The aim is to first discuss these three issues to give a picture of what gender research says concerning work organization and work health, and second to examine the theories behind the issue. In this article the female-dominated health care sector is in focus. This sector strives for efficiency relating to invisible job tasks and emotional work performed by women. In contemporary work organizations gender segregation has a tendency to take on new and subtler forms. One reason for this is today’s de-hierarchized and flexible organizations. A burning question connected to this is whether new constructions of masculinities and femininities really are ways of relating to the prevailing norm in a profession or are ways of deconstructing the gender order. To gain a deeper understanding of working life we need multidisciplinary research projects where gender-critical knowledge is interwoven into research not only on organizations, but also into research concerning the physical work environment, in order to be able to develop good and sustainable work environments, in this case in the health care sector